Finally, evidence for a momentum effect in the NBA - Arkes, J.; Martinez, J. (Journal of Quantitative Analysis in Sports, 2011)
No previous study on momentum in team sports has found any valid evidence for a momentum effect—i.e., an effect of success in the past few games, over and above the effect of team quality. We develop an econometric model to determine if there is a momentum effect in the NBA by examining how success over the past few games leads to a higher probability of winning the next game. The model takes into account the home vs. away strengths of the teams in the current game as well as their opponents in the previous games (to calculate measures of "adjusted success over the past few games"). Thus, success in previous games is adjusted for quality of the wins or losses. In addition, we account for rest days before the current game for both teams. Using data over three NBA seasons (2007-2009), we find strong evidence for a positive momentum effect.